Gut microbiota, pathogenic proteins and neurodegenerative diseases - Wei, Wei; Wang, Shixu; Xu, Chongchong; Zhou, Xuemei; Lian, Xinqing; He, Lin; Li, Kuan (Frontiers in Microbiology, 2022)
As the world's population ages, neurodegenerative diseases (NDs) have brought a great burden to the world. However, effective treatment measures have not been found to alleviate the occurrence and development of NDs. Abnormal accumulation of pathogenic proteins is an important cause of NDs. Therefore, effective inhibition of the accumulation of pathogenic proteins has become a priority. As the second brain of human, the gut plays an important role in regulate emotion and cognition functions. Recent studies have reported that the disturbance of gut microbiota (GM) is closely related to accumulation of pathogenic proteins in NDs. On the one hand, pathogenic proteins directly produced by GM are transmitted from the gut to the central center via vagus nerve. On the other hand, The harmful substances produced by GM enter the peripheral circulation through intestinal barrier and cause inflammation, or cross the blood-brain barrier into the central center to cause inflammation, and cytokines produced by the central center cause the production of pathogenic proteins. These pathogenic proteins can produced by the above two aspects can cause the activation of central microglia and further lead to NDs development. In addition, certain GM and metabolites have been shown to have neuroprotective effects. Therefore, modulating GM may be a potential clinical therapeutic approach for NDs. In this review, we summarized the possible mechanism of NDs caused by abnormal accumulation of pathogenic proteins mediated by GM to induce the activation of central microglia, cause central inflammation and explore the therapeutic potential of dietary therapy and fecal microbiota transplantation (FMT) in NDs.